ANALISIS PENDAPATAN TENAGA KERJA SEKTOR PERTANIAN PADA IFLS 5 - Damar Jati; Rifki Khoirudin (Equity: Jurnal Ekonomi, 2020)
This research was conducted with the aim to be able to find out the factors that affect the income of agricultural sector workers based on data from Indonesian family life survey wave 5 (IFLS 5) in 2014. Based on existing problems, namely the high absorption of labor in the agricultural sector but ironically the agricultural sector has the lowest level of income is from other sectors. For this reason, the writer conducts research with the title (Analysis of Factors Affecting the Income Level of Indonesian Agricultural Sector Workers). This study took a sample of 1104 respondents from the total population of the agricultural sector as much as 1891. Respondents were filtered based on productive age 15-65 years. With the dependent variable income of workers and the independent variables of education level, age, gender, working hours, marital status and work experience. From the results of the statistical tests conducted shows that 51% of the independent variables affect the independent variables and the rest are influenced by independent variables outside the research model. From the results of multiple linear regression tests indicate that the independent variables significantly influence the variables of education level, age, working hours, and work experience and can explain their influence on the labor sector income variable in Indonesia.